2022
DOI: 10.17509/ijal.v12i2.26143
|View full text |Cite
|
Sign up to set email alerts
|

Production of gutturals by non-native speakers of Arabic

Abstract: This paper investigates the production of Arabic gutturals by native (NSs) and non-native speakers (NNSs) of Arabic. A total of 40 participants, 20 NSs and 20 NNSs were recruited. 240 tokens were collected using two major methods: free speech and nonsense word testing. Using PRAAT software (version 6.1.01), the tokens were analyzed acoustically to measure F1 and F2 and to signal the (non)significance of the difference between the target groups and auditorily to rate gutturals’ production accuracy by NNSs. F1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Consequently, they resort to substituting it with the glottal /h/ sound, reducing the motor effort needed for articulation. Interestingly, several studies have shown that guttural sounds pose a significant challenge and are considered very problematic for various second language learners (Eads, Khater, & Mielke, 2018;Mashaqba, Huneety, Abu Guba, & Al-Duneibat, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, they resort to substituting it with the glottal /h/ sound, reducing the motor effort needed for articulation. Interestingly, several studies have shown that guttural sounds pose a significant challenge and are considered very problematic for various second language learners (Eads, Khater, & Mielke, 2018;Mashaqba, Huneety, Abu Guba, & Al-Duneibat, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Teenagers change a lot of lexicon patterns phonologically, morphologically and semantically for the purpose of exclusivity in their language group. Slang is created by a change in the form of linguistic messages with more emphasis on forms and intentions that aim at concealment and humor (Mashaqba, 2022). This is also according to research (Nuraeni et al, 2021) that there are seven reasons why teenagers use slang when interacting, namely enriching language, to induce friendliness, so that there are differences, facilitate association, reduce the seriousness of conversation, to have fun, and to create pleasure in virtuosity.…”
Section: Context Of Use Of Slangmentioning
confidence: 99%